The effect of positioning and diaphragmatic breathing exercises on respiratory muscle activity in people with chronic obstructive pulmonary disease - Brenda Morrow; Jarred Brink; Samantha Grace; Lisa Pritchard; Alison Lupton-Smith (AOSIS, 2016)
Background: Body positioning and diaphragmatic breathing may alter respiratory pattern and reduce dyspnoea in people with chronic obstructive pulmonary disease (COPD). Objectives: To determine the effect of positioning and diaphragmatic breathing on respiratory muscle activity in a convenience sample of people with COPD, using surface electromyography (sEMG). Methods: This prospective descriptive study recorded sEMG measurements at baseline, after upright positioning, during diaphragmatic breathing and 5 minutes thereafter. Vital signs and levels of perceived dyspnoea were recorded at baseline and at the end of the study. Data were analysed using repeated measures ANOVAs with post hoc t-tests for dependent and independent variables. Results: Eighteen participants (13 male; mean ± standard deviation age 59.0 ± 7.9 years) were enrolled. Total diaphragmatic activity did not change with repositioning (p = 0.2), but activity increased from 7.3 ± 4.2 µV at baseline to 10.0 ± 3.3 µV during diaphragmatic breathing (p = 0.006) with a subsequent reduction from baseline to 6.1 ± 3.5 µV (p = 0.007) at the final measurement. There was no change in intercostal muscle activity at different time points (p = 0.8). No adverse events occurred. Nutritional status significantly affected diaphragmatic activity (p = 0.004), with participants with normal body mass index (BMI) showing the greatest response to both positioning and diaphragmatic breathing. There were no significant changes in vital signs, except for a reduction in systolic/diastolic blood pressure from 139.6 ± 18.7/80.4 ± 13.0 to 126.0 ± 15.1/75.2 ± 14.7 (p < 0.05). Conclusion: A single session of diaphragmatic breathing transiently improved diaphragmatic muscle activity, with no associated reduction in dyspnoea. Keywords: diaphragmatic breathing, positioning, chronic obstructive pulmonary disease, physiotherapy, electromyography, breathing exercises